The Physical and Cehmical Soil Properties on Heath Forest and Ex-Tin Mined Land in East Belitung District SIFAT FISIKA DAN KIMIA TANAH DI HUTAN KERANGAS DAN LAHAN PASCA TAMBANG TIMAH KABUPATEN BELITUNG TIMUR - Dina Oktavia; Yadi Setiadi; Iwan Hilwan (Jurnal Silvikultur Tropika, 2014)
The degradation of heath forest that caused by tin mining activity effected some environmental problems such as erotion, sedimentation and lose biodiversity. Restoration is become a way to recocover the ecosystem functions. Information about soil physical and chemical properties is needed for land restoration. Soil samples were collected by cluster sampling method in heath forest and two ages succession of ex-tin mineland (less than a hundred years and more than a hundred years). Study results showed that the soils generally were low Cation Exchange Capacity (CEC), organic matter, total nitrogen, available P, macro nutrient and clay content in soil texture. However in ex-tin mineland more than a hundred years, there is a trend of increasing of clay content also some soil parameters. Natural succession supported soil development even it take a very long of time. Restoration on these soil conditions should augmented the organic matter to repare the texture and make up the CEC by applying Legume Cover Crop (LCC) and Seed Soil Augmentation (SSA) technique.Keywords : heath forest, restoration, soil properties, SSA, tin mining.